Chemical stabilization of chromate in blast furnace slag mixed cementitious materials. (November 2015) - Meena, Amanda H.; Kaplan, Daniel I.; Powell, Brian A.; Arai, Yuji
Highlights: Cement waste form saltstone technology was evaluated for chromate immobilization. Blast furnace slag was effective in reducing Cr(VI) to Cr(III) in saltstone. Microprobe analysis showed heterogeneous distribution of Cr(III) in saltstone. Chromium was effectively immobilized after <300 days of aging time. Abstract: Cement waste form (CWF) technology is among the leading approaches to disposing of metals and liquid low-level nuclear waste in the United States. One such material, saltstone, includes slag, fly ash and Portland cement to enhance the immobilization of contaminants (e.g., Cr, 99 Tc) in alkaline liquid wastes. To evaluate the stability of such redox sensitive contaminants in saltstone, the effects of slag as a source of reductant on Cr immobilization was evaluated in aged (<300 d) saltstone monoliths. Specifically, we investigated the effects of artificial cement pore waters on the Cr release and the spatially resolved Cr chemical state analysis using synchrotron based microfocused X-ray microprobe analysis. The microprobe analysis indicated the heterogeneous distribution of insoluble Cr(III)-species in saltstone. Although at most of 20% Crtotal was leached at the top few (2–3) millimeter depth, the release of Cr(VI) was small (<5%) at 5–30 mm with slight changes, indirectly suggesting that Cr is likely present as insoluble Cr(III) species throughout the depths. The study suggests that this saltstone formulation can effectively retain/immobilize Cr under the oxic field condition after ⩽300 d of aging time.